1999
DOI: 10.1097/00001888-199911000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Leadership behaviors for successful university–community collaborations to change curricula

Abstract: Effective leaders use a broad array of behaviors, but particularly emphasize the use of participative governance and culture/value-influencing behaviors. In addition, the more frequent use of these behaviors compared with the use of organizational power behaviors is important. It is helpful to perceive the project from a human-relations frame and at least one other frame. Using a leadership team can be helpful, especially in building coalitions, but the importance of the primary leader's behaviors to project o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…This might be related to their needs, demands, and expectations for fundamental modification of the structure and governing of Iranian medical schools. It might be associated with low ''uncertainty avoidance'' (i.e., the extent to which members of a society feel threatened by uncertain and ambiguous situations (Hofstede 1984)) among academic leaders, indicating their willingness to accept changes, as proposed by other investigators (Bland et al 1999;Huczynki and Buchanan 2001;Dastmalchian et al 2001;Hofstede 1996;Javidan and Dastmalchian 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to their needs, demands, and expectations for fundamental modification of the structure and governing of Iranian medical schools. It might be associated with low ''uncertainty avoidance'' (i.e., the extent to which members of a society feel threatened by uncertain and ambiguous situations (Hofstede 1984)) among academic leaders, indicating their willingness to accept changes, as proposed by other investigators (Bland et al 1999;Huczynki and Buchanan 2001;Dastmalchian et al 2001;Hofstede 1996;Javidan and Dastmalchian 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the nature of team leadership strategies which are probably required with the intent to establish a coalition in organizations. However, the effects of primary leader behaviours on the project success are stronger compared to this team strategy [25].…”
Section: Discussionmentioning
confidence: 87%
“…In addition to the four leadership styles as highlighted in this section, participative behaviour was identified by Bland et.al. (1999) as an effective approach in leading workforces in university context [25]. This leadership style is predicted to have significant effects on the empowerment of people in building positive organizational and enhancing organizational outcomes of the universities.…”
Section: Efqm (European Foundation Formentioning
confidence: 99%
“…Numerous researchers have described the importance of leadership in any curricular change effort, particularly the strengths and skills of the individual(s) leading the effort (Bland et al, 2000). Bland et al (1999) found that successful change leaders used participative and cultural/value-influencing behaviors more frequently than organizational power behaviors. The ability to model participatory, collaborative behaviors is especially important when these are the desired outcomes of the curriculum.…”
Section: Step 2: Stakeholders and Resourcesmentioning
confidence: 99%